Infusion of Artificial Intelligence for Teaching Chemistry: Perceptions of Chemistry Educators in Secondary Schools - AHMED, Abiola Tawa; IBRAHIM Abdulmuhsin (Journal of Education Technology, 2026)
Artificial intelligence (AI) has gained increasing attention in science education because of its potential to support personalized learning, intelligent tutoring, and interactive instructional environments. Teacher readiness nevertheless remains a critical factor influencing successful AI integration in classroom practice. The present study investigated secondary school Chemistry teachers’ awareness, perceptions, and utilization of AI technologies in Kwara State, Nigeria. A quantitative descriptive survey design was employed involving 207 purposively selected Chemistry teachers. Data were collected using a validated questionnaire measuring awareness of AI applications, perceptions toward AI-supported instruction, and utilization of AI in Chemistry learning. Reliability analysis produced a Cronbach’s alpha coefficient of 0.74, indicating acceptable internal consistency. Descriptive statistics were analyzed using percentages, means, and standard deviations. Findings revealed that teachers demonstrated moderate awareness and generally positive perceptions toward AI integration, particularly regarding instructional effectiveness, interactive learning, and simplification of abstract Chemistry concepts. Practical utilization of AI technologies in classroom instruction nevertheless remained relatively low, especially for automated assessment, learner monitoring, and virtual simulations. The study highlights a significant gap between teachers’ positive perceptions and actual AI implementation. Strengthened AI-oriented pedagogical training, institutional support, and educational infrastructure are therefore essential to promote effective, inclusive, and sustainable AI integration in Chemistry education.